Occupational and Environmental Safety and Health - Arezes, Pedro M.; Baptista, João S.; Barroso, Mónica P.; Carneiro, Paula; Cordeiro, Patrício; Costa, Nélson; Melo, Rui B.; Miguel, A. Sérgio; Perestrelo, Gonçalo; SpringerLink (Online service) (Cham : Springer International Publishing : Imprint: Springer, 2019)
This book presents a selection of essential issues that have been prioritized in the occupational and environmental area in 2019. It covers both research and best industrial practices in five main fields, i.e. occupational and environmental safety; occupational and environmental hygiene; occupational and environmental health; ergonomics and biomechanics; and psychosocial issues. In addition to this, other works were selected in transversal and emergency areas. Important issues in training, management, robotics, industry 4.0 have also been addressed. The different chapters aimed at covering the perspective of all involved people, such as managers, workers and OSH professionals. This book is intended as a timely reference guide and source of inspiration to OSH researchers, practitioners and organizations operating in a global and international context.
Safety management plan for equipment used in working at heights -- Risk assessment in the open pit mining industry-a short review -- Occupational accidents in Brazil and Portugal: a comparative study -- Relation between vibration/noise with the type of surface, in light vehicles, Use of data as a tool to study the health impact of drivers -- Work-related accidents in urban solid waste collection -- Virtual reality applications in the extractive industry-a short review -- Occupational accidents in the mining industry-a short review -- Safety Stream Mapping-A new tool applied to the textile company as a case study -- Analyzing and Classifying Risks: a Case-Study in the Furniture Industry -- Risk Management in Personal Transfer Activities using Aerial Baskets and Surfer Boats in Offshore Units.
Keywords: Security systems; Occupational health services; Employee health promotion; Medical informatics; Security Science and Technology; Occupational Health; Employee Health and Wellbeing; Health Informatics